Are ictal vocalisations related to the lateralisation of frontal lobe epilepsy?. Issue 2 (1st August 2000) - Janszky, J; Fogarasi, A; Jokeit, H; Ebner, A
Abstract : The purpose was to analyse whether non-speech vocalisations in seizures originating in the frontal lobe do have lateralising value. Patients were included who had undergone presurgical evaluation with ictal video-EEG monitoring at the Epilepsy Centre, had had resective epilepsy surgery involving the frontal lobe, and who had remained seizure free>1 year postoperatively. Twenty seven patients aged 1–42 years (mean 18) met the inclusion criteria. Age at epilepsy onset ranged from 1 month to 41 years (mean 7.1 years). All selected patients had a unilateral MRI detected lesion within the frontal lobe. Fifteen patients had right sided, 12 patients had left sided epileptogenic zones. Seizures recorded during EEG-video monitoring were re-evaluated to identify the occurrence of ictal vocalisations. Pure ictal vocalisations were distinguished from ictal sound productions due to motor or vegetative seizure activity (for example, cloni or respiratory sounds). Pure ictal vocalisation occurred in 11 patients of whom nine had a left frontal epileptogenic zone (p<0.01). It is concluded that ictal vocalisation could be an additional lateralising sign in frontal lobe epilepsy. The results suggest that not only speech, but vocalisation at a subverbal level also shows a left hemispheric dominance in humans.